Diversity, expression and mechanism of action of estrogen receptors in sea bream, Sparus auratus - Pinto, Patricia IS (2005)
Two estrogen receptor subtypes (ERα and ERβ) mediate most estrogen actions in vertebrates, including fishes. Furthermore in teleost fishes two ERβ genes are differentially expressed. In this thesis, an ERβ (sbERβb) was cloned from the hermaphrodite teleost fish sea bream (Sparus auratus) which added to the previously cloned sbERα and sbERβa. sbERβb specifically binds estrogen agonists and antagonists with high affinity. The three sbER genes (α, βa, βb) have a partially overlapping but differential distribution in male and female sea bream tissues and produce multiple transcripts. Two exon2 deleted sbERα variants were also identified with different tissue distribution and hormonal regulation. Estradiol-17β up-regulated the expression of sbERα and down-regulated both sbERβs in liver, suggesting a major role for ERα in vitellogenesis. Agonistic effects were identified for the “pure antiestrogen” ICI 182,780 in several estrogenic responses, probably mediated by sbERα up regulation in liver. The immunolocalization of sbER proteins in sea bream scales suggested that the calcium mobilising actions of E2 in scales are via a direct action on osteoclasts. Subtractive hybridization followed by RT-PCR demonstrated for the first time in fish testis the E2 up regulation of some typical liver E2-induced genes (e.g. vitellogenins and choriogenins).